Accelerated decoding method in fractal image coding - Qiang Wang (Electronics Letters)
Abstract To accelerate the fractal decoding process, a minimum domain block set (MDBS)‐based fast fractal decoding method is proposed here. In fractal encoding process, it is found that there exists a MDBS which can provide the best‐matched domain blocks for all range blocks. In the decoding process, MDBS is first identified before the first iteration. Then, only the range blocks inside MDBS are reconstructed in each of the first to penultimate iterations, and the computations of reconstructing the remaining range blocks outside MDBS can be saved to speedup the decoding process. Finally, all range blocks are reconstructed to obtain the decoded image in the last iteration. Experimental results show that about 5%–17% of total computations in decoding process can be saved.